Polyamines: Α bioenergetic smart switch for plant protection and development - Navakoudis, Eleni; Kotzabasis, Kiriakos (My University, 2022)
The present review highlights the bioenergetic role of polyamines in plant protection and development and proposes a universal model for describing polyamine-mediated stress responses. Any stress condition induces an excitation pressure on photosystem II by reforming the photosynthetic apparatus. To control this phenomenon, polyamines act directly on the molecular structure and function of the photosynthetic apparatus as well as on the components of the chemiosmotic proton-motive force (ΔpH/Δψ), thus regulating photochemical (qP) and non-photochemical quenching (NPQ) of energy. The review presents the mechanistic characteristics that underline the key role of polyamines in the structure, function, and bioenergetics of the photosynthetic apparatus upon light adaptation and/or under stress conditions. By following this mechanism, it is feasible to make stress-sensitive plants to be tolerant by simply altering their polyamine composition (especially the ratio of putrescine to spermine), either chemically or by light regulation.
Keywords: Abiotic stress; Stress tolerance; Photosynthesis; Polyamines; Photoadaptation; Photodevelopment